Karnataka Annual Plan 1981-82 Volume-III - Planning Commission (Planning Commission, 1980)
The main objectives of the development Programmes implemented during 19.80-81 are to increase the production of food grains and commercial crops. Particular emphasis is placed on programmes to increase the production of Pulses and Oilseeds. The developmental programmes which contribute towards increased production are being implemented satisfactorily. The Kharif season started on a good note. But there has been some loss due to heavy rains in coastal and monad regions while drought conditions prevailed in certain Northern and Central Districts of the State. As a result the Kharif crops suffered. The recent rains have revived the crops to some extent. The progress under some of the important programmes are explained below briefly. The World Bank aided Agricultural Extension Project which was initiated in 1978-79 and was in operation in 12 districts during 1979-80 has now been extended to the remaining 7 districts. Thus all the 19 districts in the State have been covered under the Agricultural Extension Project.
Sector wise Programmes of Development
Government of Karnataka Planning Department
Keywords: Karnataka Annual Plan 1981-82; Horticulture; Agricultural Statistics; Storage and Warehousing; Drought Prone Area Programme; Integrated Rural Development; Ground Water Survey; Karnataka Dairy Development Corporation; Agricultural Financial Institutions; Mining and Metallurgical Industries; Water and Power Development; Employment Affirmation Scheme